Brexit geographies of transnational education: uncertainty, `global Britain' and European (re-)integration - Jana M. Kleibert (Territory, Politics, Governance, 2020)
Higher education in the UK constitutes an important (export) sector that depends on mobilities of capital, labour and students. This article contributes to 'Brexit geographies' by exploring how the economic geographies of British transnational education are reconfigured during uncertainty over Brexit through spatial strategies of universities. Based on qualitative research and in-depth interviews with decision-makers in higher education in the UK, it maps the investments and analyses the rationales, narratives and spatial imaginaries motivating the construction of universities' physical presences abroad. Decision-makers' imagined futures for UK universities, first, reveal a linking to discourses of 'Global Britain' and, second, efforts towards European (re-)integration through campus development in European Union territory. The latter is intended by some to ameliorate risks of regulatory changes and provide an 'insurance policy' against the anticipated financial consequences of Brexit. However, the resulting geographies of risk and vulnerability are unevenly distributed and seem likely to increase the hierarchically structured (economic) geographies of higher education.
Keywords: 300; Brexit; uncertainty; spatial imaginaries; transnational education; international branch campus; European Union